Effects of vibration-induced fatigue on the H-reflex. (April 2018) - Sammali, F.; Xu, L.; Rabotti, C.; Cardinale, M.; Xu, Y.; van Dijk, J.P.; Zwarts, M.J.; Del Prete, Z.; Mischi, M.
Abstract: Vibration exercise (VE) has been suggested as an effective training for improving muscle strength and coordination. However, the underlying physiological adaptation processes are not yet fully understood, limiting the development of safe and effective exercise protocols. To better understand the neuromuscular responses elicited by VE, we aimed at investigating the acute effects of superimposed vibration on the Hoffmann reflex (H-reflex), measured after fatiguing exercise. Twenty-five volunteers performed four isometric contractions of the right Flexor Carpi Radialis (FCR) with baseline load at 80% of their maximal voluntary contraction (MVC), both with no vibration and with superimposed vibration at 15, 30, and 45 Hz. Fatigue was estimated by MVC test and estimation of electromyographic spectral compression. H-reflex suppression was estimated as the relative decrease after exercise. Our results show that fatiguing exercise determined a decrease in H-reflex amplitude compared to rest condition while vibration determined a lower H-reflex suppression as compared to no vibration. The superimposition of 30-Hz vibration determined the largest acute reduction in force generating capacity (36 N, p < 0.05) and the lowest H-reflex suppression (20%, p < 0.05). These results suggest VE to be particularly suitable in rehabilitation programs for rapid restoration of muscle form and function after immobilization periods.